The Big Fish - Pitts , Sorrel (Penguin Random House UK - Ladybird, 2019)
The Big Fish, a Starter level Reader, introduces phonics and sight words. Each book contains two versions of the story: the first with single words focusing on phonics, with the emphasis on letter recognition and pronunciation; the second with short sentences introducing sight words.